A study of electrochromiс Ni(OH)2 films obtained in the presence of small amounts of aluminum - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2019)
The research is related to the synthesis of electrochromic films of nickel hydroxide with aluminum as a dopant. Films were deposited via cathodic template synthesis in the presence of polyvinyl alcohol from solutions containing 0.01 M Ni(NO3)2 and Al(NO3)3. Aluminum nitrate was added in different concentrations: 0.138, 0.257 and 0.550 mM. The necessary aluminum concentration was calculated based on the theoretical grounding with the use of Faraday’s law equation. All of the prepared films demonstrated electrochemical activity, and the film deposited from the solution containing 0.01 M Ni(NO3)2 and 0.138 mM Al(NO3)3 has demonstrated the best results. The film cycled reversibly with the coloration degree of – 81 %. At the same time, the film prepared under the same conditions without the dopant demonstrated the coloration degree of 75.8 %. All films deposited in the presence of aluminum had lower switching, especially bleaching, speed in comparison to the undoped reference sample. Morphology study of the prepared films revealed that the latter differs little. The film deposited in the presence of 0.138 mM Al(NO3)3 had spherical formations on its surface. It was also found that the morphology of the substrate, which was glass coated with SnO2:F, differed significantly from the morphology of the films deposited with and without the dopant. The film deposited from the solution of 0.01 M Ni(NO3)2 and 0.138 мМ Al(NO3)3 was confirmed to contain aluminum. The mass ratio of aluminum to nickel in the Ni–Al-138 film varied between 1:10.23 and 1:6.44.